The Effect of Pineapple Juice (Ananas Comosus) on Dysmenorrhea Pain - Siti Maimuna Bin Gani; Rani Safitri; Nila Widya Keswara (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Menstrual pain, also known as dysmenorrhea, is one of the most common reproductive health problems experienced by adolescent girls. This condition often recurs every month and can interfere with school attendance, concentration, and participation in daily activities. Many individuals choose pharmacological treatments such as analgesics to relieve symptoms. However, excessive use of pain relievers can lead to side effects, prompting interest in non-pharmacological approaches. One such approach is the consumption of pineapple juice, which contains beneficial compounds such as pectin, vitamin C, and the enzyme bromelain. Bromelain has anti-inflammatory properties, aids in muscle relaxation, and improves blood circulation, potentially reducing uterine muscle contractions that cause pain. This study aimed to determine the effect of pineapple juice consumption on reducing menstrual pain among adolescent girls. The research design used was pre-experimental with a pretest–posttest approach. The population included 121 adolescent girls who experienced menstrual pain, and the sample was obtained through accidental sampling. Pain quality was evaluated using observation sheets, while pain intensity was measured with the Numeric Rating Scale (NRS), which has a validity coefficient of r = 0.90 and reliability above 0.95. Before the intervention, the majority of respondents reported a pain intensity score of 6 (46.7%), with a mean score of 5.86. Following the administration of pineapple juice, pain intensity predominantly decreased to a score of 4 (86.6%), with a mean score of 3.06. The Wilcoxon test produced a p-value of 0.000 (<0.05), indicating a statistically significant difference between pre- and post-intervention pain levels. In conclusion, pineapple juice is effective in significantly reducing menstrual pain in adolescent girls. This finding supports its potential as a simple, affordable, and natural alternative to pharmacological treatments. Further research with a control group and larger sample size is recommended to strengthen the evidence.